Audit of the accuracy of the UK Registry of Endocrine and Thyroid Surgery. (1st March 2022) - Cooper, Duncan; Aspinall, Sebastian; Hay, Ashley; Adamson, Richard; Nixon, Iain
Abstract: Background: Clinician-inputted data is collected in the UK Registry of Thyroid Surgery (UKRETS) on endocrine operations performed by members of the British Association of Thyroid Surgeons (BAETS) and analyses of the data published annually in the Surgeon Specific Outcome Reports, National Audit Report and peer reviewed journals. However, UKRETS has never been externally validated. The aim of this study is to assess the accuracy of data reported in the UKRETS. Methods: Retrospective audit of the accuracy of data in UKRETS for all thyroid operations performed by two surgeons from a single centre between 1/7/2016-30/6/2019. UKRETS data was compared with data extracted by an independent assessor from hospital Electronic Patient Records (EPR). Results: 204 patients were analysed. 91 (44.6%) had total thyroidectomy, 101 (49.5%) thyroid lobectomy and 34 (16.7%) neck dissection +/- thyroidectomy. 4080 data points from UKRETS were analysed. 94.0% (3835/4080) were accurate when compared to EPR. Pre-operative data was the least accurate 91.9% (937/1020) and peri-operative data was the most accurate 97.7% (997/1020). Post-operative and follow-up data had accuracies of 93.8% (957/1020) and 92.5% (944/1020) respectively. Date of operation was the most accurate, 99.0% (202/204) and date of discharge the least, 89.0% (182/204). Conclusions: This study is the first external validation of data in the UKRETS and, while limited in number of surgeons / single centre, suggests that current data collection in UKRETS is accurate, particularly for peri-operative data. Further validation across multiple centres needs to be undertaken to confirm these findings.